Indomethacin-induced oxidative stress enhances death receptor 5 signaling and sensitizes tumor cells to adoptive T-cell therapy. Issue 7 (26th July 2022) - Aboelella, Nada S; Brandle, Caitlin; Okoko, Ogacheko; Gazi, Md Yeashin; Ding, Zhi-Chun; Xu, Hongyan; Gorman, Gregory; Bollag, Roni; Davila, Marco L; Bryan, Locke J; Munn, David H; Piazza, Gary A; et al.
Abstract : Background: Adoptive cell therapy (ACT) using genetically modified T cells has evolved into a promising treatment option for patients with cancer. However, even for the best-studied and clinically validated CD19-targeted chimeric antigen receptor (CAR) T-cell therapy, many patients face the challenge of lack of response or occurrence of relapse. There is increasing need to improve the efficacy of ACT so that durable, curative outcomes can be achieved in a broad patient population. Methods: Here, we investigated the impact of indomethacin (indo), a non-steroidal anti-inflammatory drug (NSAID), on the efficacy of ACT in multiple preclinical models. Mice with established B-cell lymphoma received various combinations of preconditioning chemotherapy, infusion of suboptimal dose of tumor-reactive T cells, and indo administration. Donor T cells used in the ACT models included CD4 + T cells expressing a tumor-specific T cell receptor (TCR) and T cells engineered to express CD19CAR. Mice were monitored for tumor growth and survival. The effects of indo on donor T cell phenotype and function were evaluated. The molecular mechanisms by which indo may influence the outcome of ACT were investigated. Results: ACT coupled with indo administration led to improved tumor growth control and prolonged mouse survival. Indo did not affect the activation status and tumor infiltration of the donor T cells. Moreover, the beneficial effect of indo in ACT did not rely on its inhibitory effect on the immunosuppressive cyclooxygenase 2 (COX2)/prostaglandin E2 (PGE2) axis. Instead, indo-induced oxidative stress boosted the expression of death receptor 5 (DR5) in tumor cells, rendering them susceptible to donor T cells expressing TNF-related apoptosis-inducing ligand (TRAIL). Furthermore, the ACT-potentiating effect of indo was diminished against DR5-deficient tumors, but was amplified by donor T cells engineered to overexpress TRAIL. Conclusion: Our results demonstrate that the pro-oxidative property of indo can be exploited to enhance death receptor signaling in cancer cells, providing rationale for combining indo with genetically modified T cells to intensify tumor cell killing through the TRAIL-DR5 axis. These findings implicate indo administration, and potentially similar use of other NSAIDs, as a readily applicable and cost-effective approach to augment the efficacy of ACT.